The Physiological and Perceptual Stress Response During Data Collection in Altitude: A Single-Case Report of A Healthy Researcher - Freitag, Livia; Clijsen, Ron; Hohenauer, Erich (Archives of Clinical and Medical Case Reports, 2021)
Environmental conditions such as altitude exposure can lead to diverse physiological adjustments and stimulate a kind of stress response which can be measured with validated biomarkers. Stress negatively affects the cognitive performance and potential increases source of error. The aim of the following case study is to evaluate the physiological stress response of a healthy researcher during the conduct of an extraordinary study in altitude. The study was performed at an altitude of nearly 3000 meters above sea level in a mountain laboratory. Data were compared to conditions in a professional research laboratory and office at 550 meters above sea level. Parameters were mitochondrial activity, salivary cortisol, stress level and body battery collected by a smartwatch and scores of the daily stress inventory questionnaire. Almost all results showed a similar pattern: Outcomes were slightly impaired during laboratory conditions (LAB), compared to a normal office day in research (NOR). The highest impact on all measured values were observed on the first day of altitude exposure (M1), followed by a recovery until the last mountain day (M4). On the last day (POST), data returned to the level of NOR condition. The results of this case report show, that researching in altitude exposure can lead to an increased stress response. Particularly during data collection in such extraordinary study conditions, great attention must be given to prevent errors. Previously performed acclimatization procedures on the researcher might influence the results.